Progression of Parapapillary Choroidal Microvascular Dropout After Disc Hemorrhage in Glaucoma Patients: 2 Case Reports. Issue 1 (January 2021) - Lee, Jong Sub; Lee, Won June; Lim, Han Woong; Seong, Mincheol
Abstract : Purpose: Microvasculature dropout (MvD) is a novel finding seen in optical coherence tomography angiography (OCTA), which is characterized by a localized dehiscence of the choriocapillaris in the parapapillary atrophy area. Disc hemorrhage (DH) is an important factor often associated with the development and especially progression of glaucoma. Here, we present 2 cases of MvD progression with DH. Methods and Results: Case 1: A 62-year-old female patient with normal tension glaucoma in both her eyes had recurrent DH at the inferior area of her right eye. A new DH was observed in the inferotemporal area of the right eye with MvD progression on OCTA in the same direction three months from the baseline. Case 2: A 57-year-old female patient with bilateral steroid-induced secondary glaucoma also had recurrent DH in her right eye. Four months from the baseline, DH occurred in the superotemporal and inferotemporal area of the right eye, and MvD was detected on OCTA in the superotemporal corresponding direction. After 19 months from the baseline, OCTA was repeated. The DH had resolved, but the superotemporal MvD persisted. Conclusions: The 2 cases presented here are the first to report on the relationship between MvD progression and DH. MvD as visualized in OCTA imaging looks to be of clinical importance, and hopefully future studies will reveal the actual connection between MvD, DH, and glaucoma progression. Abstract : Supplemental Digital Content is available in the text.